Sistem Pendukung Keputusan Dalam Menentukan Penerima Bantuan Langsung Tunai Dengan Metode Profile Matching Pada Kantor Kepala Desa Narigunung 1 - Adi Ebenezer Silitonga; Agustina Simangunsong (Program Studi Teknik Informatika, Fakultas Teknik. Universitas Serambi Mekkah, 2020)
The government provides direct cash assistance for the community, which originates from the Village Fund or called BLT-Dana Desa. The criteria for BLT recipients were very clear in writing. From the data collected, the aspects and criteria for BLT recipients were determined. The Profile Matching method or profile matching is applied to the calculation of the assessment gap in decision makers. Weighting in the Profile Matching method is a definite value that is firm on certain values because the values are members of a crisp set. In a strict set, the membership of an element in the set is expressly stated whether the object is a member of the set or not by using the characteristic function. Identification of problems in community research wants transparency and equality of BLT recipients for residents who do not earn. Different criteria emerged from the opinions of villagers in determining BLT recipients. Implementation of data collection and distribution of BLT-Village Funds that are effective, efficient, and right on target. The determination of recipients of BLT funds was supported by an assessment of Aspects and Criteria. The application design uses the PHP programming language and Xampp database management by applying the profile matching method.